Pengalaman Komunikasi Keluarga dalam Menanamkan High Order Thinking Skills pada Anak Berprestasi di SMP Negeri 1 Padang - Syafira Natasya; Emeraldy Chatra; Elva Ronaning Roem (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
The presence of a healthy family communication is crucial in instilling High Order Thinking Skills  in children. That is why we need to seek insights from families who have implemented such communication. The purpose of this research is to explore the experiences of family communication in cultivating High Order Thinking Skills  in high-achieving students at SMP Negeri 1 Padang. This study employs a qualitative method with Edmund Husserl's phenomenological approach. The research findings reveal that the experiences of family communication in instilling High Order Thinking Skills  in high-achieving students at SMP Negeri 1 Padang include open and collaborative discussions with children to stimulate their reasoning abilities, storytelling with children about emotionally engaging narratives to develop reflective thinking, communicating with empathy to build strong emotional bonds with children, conveying well-directed boundaries to foster analytical and critical evaluation skills in children, creating a comfortable atmosphere for communication to establish a solid parent-child bond, actively listening to children's stories with undivided attention to encourage their ability to express opinions, engaging in bedtime and school departure conversations to sharpen children's creative thinking, and interactive deep talks to encourage alternative thinking and innovative solutions in children.